Dział administracji rządowej ,,informatyzacja” – aspekty strukturalno-ustrojowe - Maciejewski, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The concept of the administrative government department has changed the previously used concept of a resort. Different government administrations group closely issues connected with the government administration. The Prime Minister entrusts managing of a department to a minister by means of an attributive regulation. One of administrative departments is “Informatization” which embraces generally the management of IT solutions. In connection with a rapidly developing technology its importance is increasing. We can also observe a dynamic rise of issues within the scope of it. Pandemic conditions exposed practical dimensions of informatization.
Keywords: government administration; administrative government department; attributive act; informatization